A performance measurement system for academic entrepreneurship: a case study. Issue 3 (12th August 2014) - Secundo, Giustina; Elia, Gianluca
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims at proposing a performance measurement system (PMS) for academic entrepreneurship. Design/methodology/approach – The PMS has been developed through action research carried out within an Italian higher education and research centre on the basis of the literature background, focus groups and interviews. Findings – The study presents a new PMS based on an input–output model for academic entrepreneurship. As a result, a multidimensional framework for measuring technology entrepreneurship is proposed together with a set of key performance indicators (KPIs) to assess the "third mission" of universities. The application of the framework allows demonstration of its validity in public settings. Research limitations/implications – Because the research was conducted in a specific organisation, the possibility of generalizing the results to similar institutions is a key issue. Hence, it is important to distinguish between what is general in scope and what is case-specific. Practical implications – This study contributes to the extant literature on performance measurement of entrepreneurship process within research and higher education institutes that is traditionally focussed at the firm level. From a practitioner perspective, the model can be used both by universities which are interested in measuring their entrepreneurial capital and by other stakeholders who are interested in evaluating the value generation performances of universities. Implications for the society are clarified as well. Social implications – As for the society, the proposed model allows evaluation of the university's pivotal role in the social and economic development of the region where it is located, especially in terms of new employments and new technology-intensive firms. Originality/value – The PMS is developed according to a process-oriented perspective of the academic entrepreneurship by identifying, for each step, a set of KPIs to meet the information needs of different stakeholders. The proposed PMS allows monitoring each phase of the technology entrepreneurship and managing the results in terms of social and economic impact developed. Contributions in PMS and intellectual capital literature are identified.